2018
DOI: 10.5455/aim.2018.26.46-50
|View full text |Cite
|
Sign up to set email alerts
|

The Framework of NICU-discharge Plan System for Preterm Infants in Iran: Duties, Components and Capabilities

Abstract: Introduction:The development of comprehensive discharge plan system Not only, will facilitate the discharge process, increase staff and parent satisfaction, improve the care of preterm infants, also reduce the human error.Aim:to determine duties, components and capabilities of NICU discharge plan system as a multidimensional tool for facilitating the complex process of transition preterm infants to the home and support parents for post-discharge care.Method:The descriptive and qualitative study conducted in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Encouraging parents to prepare for discharge and look for available resources more proactively is the first and the essential step to promote discharge preparation of preterm infants currently (American Academy of Pediatrics Committee on & Newborn, 2008; Smith et al., 2013). A checklist or brochure could help parents learn about the importance of discharge preparation, their role during the process and what to prepare before discharge (American Academy of Pediatrics Committee on & Newborn, 2008; Seyedfarajollah, Nayeri, Kalhori, Ghazisaeedi, & Keikha, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging parents to prepare for discharge and look for available resources more proactively is the first and the essential step to promote discharge preparation of preterm infants currently (American Academy of Pediatrics Committee on & Newborn, 2008; Smith et al., 2013). A checklist or brochure could help parents learn about the importance of discharge preparation, their role during the process and what to prepare before discharge (American Academy of Pediatrics Committee on & Newborn, 2008; Seyedfarajollah, Nayeri, Kalhori, Ghazisaeedi, & Keikha, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…High-quality discharge teaching conducted by nurses is an important component of this smooth transition and would help parents to prepare for their preterm infant's discharge (Jefferies, 2014;Raphael et al, 2018;Seyedfarajollah et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In some countries such as the USA, Canada and Iran, recommendations on how to prepare for the preterm infants' discharge with their families, including appropriate investigations and screening tests, resolved medical concerns, and individual follow-up plans, could effectively improve RHD of the parents. (Jefferies, 2014;Seyedfarajollah et al, 2018).…”
Section: F I G U R E 2 Mediation Models and Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental discharge education usually begins while the infants are in NICUs, aiming at providing anticipatory guidance and information to help parents successfully care for the infant at home (8) . Meanwhile, many strategies have been established to improve the effectiveness of discharge education programs (9) , researchers found that education programs for parents of preterm infants during the hospitalization period contributed to higher levels of parental knowledge of parenting infants, more parental satisfaction with nursing service (10) , lower infant morbidity after discharge (11) and lower readmission rates (12) . Despite receiving training by neonatal nurses, mothers of preterm infants encounter difficulties at home, hospital readmission rates increase and family life is disrupted (13) .…”
Section: Introductionmentioning
confidence: 99%